PENGARUH KOMUNIKASI ORGANISASI, MOTIVASI DAN KOMPENSASI TERHADAP KEPPUASAN KERJA KARYAWAN UD MITRA JAYA FARM - Bukori, Imam; Zulistiani, Zulistiani; Wisnu Setya, Sigit (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study was to analyze whether there was a significant effect of the variables of organizational communication, motivation and compensation partially or simultaneously on employee satisfaction at UD Mitra Jaya Farm. The approach used in this research is a quantitative approach and the type of causal relationship research, with the sampling technique using the Slovin formula, the sample size used is 50 employees, and the data analysis technique using descriptive statistics, classical assumption test, multiple linear regression, coefficient of determination, and hypothesis testing using SPSS Version 25 software. The results showed that there was a significant effect of organizational communication and compensation variables, no significant influence of motivational variables, and there was a significant influence of organizational communication, motivation and compensation variables simultaneously on employee satisfaction at UD Mitra Jaya Farm.